2015
DOI: 10.1523/jneurosci.3219-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Recollection-Related Increases in Functional Connectivity Predict Individual Differences in Memory Accuracy

Abstract: Recollection involves retrieving specific contextual details about a prior event. Functional neuroimaging studies have identified several brain regions that are consistently more active during successful versus failed recollection-the "core recollection network." In the present study, we investigated whether these regions demonstrate recollection-related increases not only in activity but also in functional connectivity in healthy human adults. We used fMRI to compare time-series correlations during successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
141
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(162 citation statements)
references
References 45 publications
18
141
2
Order By: Relevance
“…This finding supports a recent study (King et al, 2015) that found across three experiments that the magnitude of recollection-related increases in connectivity predicted recollection accuracy. Task-related functional connectivity studies have shown that during episodic encoding higher performing older adults have greater functional connectivity between hippocampal activity and activity in the dorsolateral prefrontal and parietal cortex (Grady et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…This finding supports a recent study (King et al, 2015) that found across three experiments that the magnitude of recollection-related increases in connectivity predicted recollection accuracy. Task-related functional connectivity studies have shown that during episodic encoding higher performing older adults have greater functional connectivity between hippocampal activity and activity in the dorsolateral prefrontal and parietal cortex (Grady et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…Alternate accounts of the present findings might suggest that enhanced HPC connectivity with prefrontal regions during learning reflects other operations such as inhibition (Aron et al, 2014) or retrieval (Schedlbauer et al, 2014; King et al, 2015) of the related A item (without integration). With regards to an interpretation based on inhibition, it is worth noting that such functions have typically been ascribed to right lateral PFC; as such, it is unclear whether MPFC would be expected to perform a similar operation.…”
Section: Discussionmentioning
confidence: 77%
“…These regions, along with the parahippocampal cortex, are structurally interconnected via the cingulum bundle (Mufson and Pandya, 1984; Kravitz et al, 2011) and show highly correlated activity fluctuations during the resting state (Kahn et al, 2008; Vincent et al, 2006; Buckner et al, 2008; Greicius et al, 2009; Uddin et al, 2010; Libby et al, 2012; Ritchey et al, 2014). In addition to being co-activated during episodic retrieval tasks, functional connectivity between regions in the core recollection network is increased during successful recollection (King et al, 2015). Beyond recognition tasks, regions in the core recollection network are also reliably co-activated during tasks that require autobiographical memory retrieval (see Svoboda et al, 2006), prospective thinking (e.g., Addis et al, 2007; Schacter et al, 2007), imagination/scene construction (Hassabis and Maguire, 2007, 2009), or spatial navigation in virtual environments (Burgess et al, 2001; Hartley et al, 2003; Spreng et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this network of cortical areas is consistently co-active with the hippocampus during recollection-based episodic retrieval that entails conscious reinstatement of contextual details of a past event (Spaniol et al, 2009; Kim, 2010; Rugg and Vilberg, 2013). Co-activation of these areas during episodic retrieval might indicate that these cortical areas work in concert to support the recovery of the temporal and spatial context of a past event (King et al, 2015; Schedlbauer et al, 2014). Put another way, neocortical recollection network regions might structure temporal as well as spatial processing in episodic memory.…”
Section: Introductionmentioning
confidence: 99%